EVALUATION OF ACTIVITIES WITH INDIVIDUAL PLANTS POSSESSING INSECTICIDAL PROPERTIES FOR THE CONTROL OF THE PEA WEEVIL (Bruchidius incarnates Boh.) IN THE SHIRAK REGION - Petrosyan, K.; Sargsyan, E. (SUSh Scientific Proceedings, 2025)
The use of chemical plant protection products can significantly reduce the number of harmful insects, plant pathogens and weeds, as well as the extent of damage they cause. However, unreasonable doses and regular use of pesticides cause a number of negative consequences, and, above all, disruption of the biological balance in agrocenoses, weakening of the biological activity of the soil, mass reproduction of insects, which, due to their limited distribution, previously did not cause much harm or were even harmless. The effectiveness of herbal preparations lies in reducing the risk to human health and the destruction of the environment. The article presents the research of the lifestyle and prevalence of the pea weevil (Bruchidius incarnatus), one of the pests of pea (Cicer arietinum L.), a common crop in the agrosystems of the Shirak region, during its vegetation period, which were carried out in the grain-producing areas of the Gyumri Breeding Station CJSC of the Ministry of Energy of the Republic of Armenia in field conditions in 2023 and 2024. Effective methods for controlling pea weevils using plants with insecticidal properties, such as black currant (Ribes nigrum L.) and common tomato (Lycopersicum esculentum Mill.), of the varieties widespread in Armenia (Tomato mandur L.), were proposed. This provided an average biological efficiency of 77.2% for tomato and 62.6% for black currant in 2023 and 2024. Considering the above, the proposed products are more environmentally friendly and are an alternative to chemical means of protection. Thanks to this, the issues of environmental cleanliness, biodiversity and public health safety are resolved. Thus, we recommend refraining from using chemicals and fighting the pea weevil with plants with insecticidal properties, such as common tomato and black currant. The article also provides the corresponding doses of the working solution based on the area of the studied territories (in ha/l).